2018
DOI: 10.12968/bjca.2018.13.4.182
|View full text |Cite
|
Sign up to set email alerts
|

Patients' satisfaction with information at discharge

Abstract: Background: Adequate patient knowledge and engagement with their condition and its management can reduce re-hospitalisations and improve outcomes after acute admission for circulatory system disease. Aim: To evaluate the perceptions of cardio-or cerebrovascular patients of their satisfaction with discharge processes and to determine if this differs by demographic groups. Methods: A sample of 536 eligible public hospital inpatients was extracted from a consumer experience surveillance system. Questions relating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Patient‐centred communication adapted to individual needs has previously been shown to contribute to perceptions of overall satisfaction with the care experience (Esmaeili et al, 2016 ; Franzon et al, 2018 ; Harrison et al, 2017 ). Similar to Harrison et al ( 2017 ), the findings from this study suggest that patients' positive perceptions of their care experience were influenced by whether they felt well‐informed about their procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient‐centred communication adapted to individual needs has previously been shown to contribute to perceptions of overall satisfaction with the care experience (Esmaeili et al, 2016 ; Franzon et al, 2018 ; Harrison et al, 2017 ). Similar to Harrison et al ( 2017 ), the findings from this study suggest that patients' positive perceptions of their care experience were influenced by whether they felt well‐informed about their procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified that the provision of information to patients in written form only, such as a discharge instruction sheet, may lead to sub‐optimal outcomes because patients do not typically have the appropriate skills or knowledge to effectively self‐care (Horwitz, 2017 ). In particular, Franzon et al ( 2018 ) identified lower levels of satisfaction with written discharge instructions for those aged ≥80 years, females, and those with higher levels of health literacy. Provision of both verbal and written discharge information may be beneficial in communicating key information and minimizing misunderstanding (Theodoridis et al, 2020 ), standardizing the processes for discharge education (Kang et al, 2020 ), and better preparing patients for discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite clinical guideline recommendations and updates, it seems that the amount of rehabilitation, intensity, and frequency needs remain unmet globally. A recent mixed-method study by Clark et al [ 32 ] identified information exchange (one-to-one and in groups) as the pre-eminent determinant of the number of therapy sessions and their effectiveness. Although some therapists show an understanding of the evidence underpinning the recommendations for increasing therapy time, staff levels (i.e., low HCP-to-patient ratios) preclude their ability to deliver a sufficient duration of therapy for all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it allows patients to understand the diagnosis and treatment options (Lim and Low, 2017). On the other hand, adequate patients' information and their engagement in treatment regimen will minimize re-hospitalizations and improve the outcome of their disease (Franzon et al, 2018).…”
Section: Itemsmentioning
confidence: 99%